AI IN EVERYDAY LIFE - Christophoridis, George; Vrettos, Anastasis; Kiriakou, Odisseas (Open Schools Journal for Open Science, 2025)
Artificial Intelligence (AI) has become deeply integrated into our daily routines, affecting areas ranging from personal communication to transportation and entertainment. With its ability to simulate human intelligence, AI supports virtual assistants, enhances healthcare diagnostics, optimizes traffic, and personalizes digital experiences. This presentation explores the various dimensions in which AI contributes to and transforms everyday life.